2008
DOI: 10.4028/www.scientific.net/amr.44-46.189
|View full text |Cite
|
Sign up to set email alerts
|

Journal Bearing Wear Monitoring via On-Line Visual Ferrography

Abstract: Wear condition of journal bearing was experimentally monitored with an On-Line Visual Ferrograph (OLVF) system. The round bearing was made of 45# steel with babbitt alloy bushing and the bearing journal was made of 45# steel. High stress of the water content of 0%,1%,3% in lubricant, 10 times of a normal load of 2200 N, and the rotating speeds at 500, 1000, 2000 rpm were adopted in accelerated experiment. A quantitative index of particle coverage area (IPCA) together with wear debris ferro-image was used to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…It can effectively monitor the wear state and lubrication state of the friction pairs [68]. At present, the technology of ferrography, [69], spectrum, [70] and related physical and chemical analysis [71][72] are used. Some off-line methods that are inefficient and inevitable delays cannot meet the demand of real-time online detection, and online analysis is the inevitable trend of state analysis.…”
Section: Oil Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It can effectively monitor the wear state and lubrication state of the friction pairs [68]. At present, the technology of ferrography, [69], spectrum, [70] and related physical and chemical analysis [71][72] are used. Some off-line methods that are inefficient and inevitable delays cannot meet the demand of real-time online detection, and online analysis is the inevitable trend of state analysis.…”
Section: Oil Analysismentioning
confidence: 99%
“…The application of the aero engine proved the feasibility and application potential of the on-line wear particle analysis. Wu et al [69] utilized the online ferrography for radial bearings for wear condition monitoring in different conditions, and used ICPA to evaluate the wear condition. Test results showed that the IPCA value accords with bathtub curve, and the main wear mechanisms are micro cutting and plough.…”
Section: Oil Analysismentioning
confidence: 99%
“…The values of k and P were calculated by substituting the raw data into equations (21) and (22). The correction monitoring data (IPCAold) was then calculated.…”
Section: Experimental Set-up Of Test-amentioning
confidence: 99%
“…Nikolakopoulos and Papadopoulos [13] established a sliding bearing wear analysis, which can be applied to study the relationship between friction, angle of displacement, wear depth, and wear-related power consumption. Wu et al [14] studied the wear mechanism of sliding bearings involving various moisture contents and rotating speeds. Comparative experimental studies on the friction properties and wear mechanism of different materials of sliding bearings under different working conditions have also been studied [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%